2013
DOI: 10.1089/sur.2012.044
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Colonization by Multi-Drug-ResistantAcinetobacter calcoaceticus–A. baumanniiComplex and Changes in Antimicrobial Susceptibilities in Surgical Intensive Care Units

Abstract: Not only patients or healthcare workers, but also medical equipment, might have carried the predominant outbreak strain from the old district to the new building. Therefore, even in a new environment, infection control programs must be enforced continually, and healthcare providers must be educated repeatedly to prevent recurrent outbreaks of MDR-ACB infection in the hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…baumannii, which is a gram-negative, non-fermentative coccobacillus of the family Moraxellaceae, is considered to be an important cause of ventilator-associated pneumonia, sepsis, urinary system infection and meningitis (11)(12)(13)(14)(15)(16)(17) (18). We speculated that this descrepency may be due to the strains selected in this study.…”
Section: Discussionmentioning
confidence: 87%
“…baumannii, which is a gram-negative, non-fermentative coccobacillus of the family Moraxellaceae, is considered to be an important cause of ventilator-associated pneumonia, sepsis, urinary system infection and meningitis (11)(12)(13)(14)(15)(16)(17) (18). We speculated that this descrepency may be due to the strains selected in this study.…”
Section: Discussionmentioning
confidence: 87%
“…Study of an outbreak caused by MDR Acinetobacter calcoaceticus-A. baumannii complex in a surgical intensive care unit showed that patients, healthcare workers as well as medical equipments carried the predominant strain responsible for the outbreak [5]. Various molecular methods like enterobacterial repetitive intergenic consensus (ERIC)-PCR, PFGE and multilocus sequence typing (MLST)-PCR have demonstrated the genetic similarity of A. baumannii isolates from patients and their immediate environments [10].…”
Section: Discussionmentioning
confidence: 99%
“…Sample preparation followed the protocol described previously [11,24]. Each isolated sample was collected into a sterile tube or container (except blood culture samples, which were inoculated immediately in blood culture-specific bottles (BD BACTEC TM ; Becton Dickinson, Franklin Lakes, NJ, USA), sent to the laboratory within two to three hours of collection, and maintained at room temperature.…”
Section: Bacterial Cultures and Identificationsmentioning
confidence: 99%
“…This development makes the treatment of patients infected with these pathogens difficult, and consequently increases morbidity and mortality [1,6]. Notably, although carbapenems have been used as the main antimicrobial therapy for multidrug-resistant (MDR)-ACB and MDR-P. aeruginosa [7,8], carbapenem resistance has also emerged in these two bacterial species and caused severe nosocomial outbreaks [9][10][11]. These lines of evidence indicate that an increase in antibiotic prescription is closely related to elevated antimicrobial resistance rates.…”
Section: Introductionmentioning
confidence: 99%